10 the essential rules for beating the market - Turner, Michael K. 1947- (John Wiley & Sons, 2009)
"10 takes you step by step through the process of creating a market-beating stock portfolio, and shows you how to trade stocks using a combination of both fundamental and technical analysis. With this book as your guide, you'll quickly learn how to get into a stock at the right time and, more importantly, when to exit that position. You'll also discover how to view the market and interpret what is happening on a broader scale, so you can maximize profits on individual positions and boost the overall performance of your portfolio"--Resource description page
Print version record
Keywords: Investments; Speculation; Investissements; Spéculation; speculating; BUSINESS & ECONOMICS; Investments & Securities; General